A Zn4 cluster as a bi-functional luminescence sensor for highly sensitive detection of chloride ions and histidine in aqueous media. Issue 23 (31st May 2022) - Li, Jing; Ma, Ke-Xin; Yang, Yan; Yang, Hua; Lu, Jing; Li, Da-Cheng; Dou, Jian-Min; Ma, Hui-Yan; Wang, Su-Na; Li, Yun-Wu
Abstract : A novel Zn4 cluster can efficiently detect Cl − and histidine with low LODs in various aqueous media. The sensing mechanism of Cl − is revealed by various experimental methods and DFT calculations. Abstract : The luminescence sensor is one of the most effective devices for monitoring environmental pollution. By combining precise structures and defined functional sites, luminescent coordinated metal clusters (LCMCs) can allow mechanism-based luminescence sensing optimization. Here, a Zn4 cluster has been fabricated by introducing uncoordinated N-, OH-dual hydrogen-bonding active sites as well as coordination of unsaturated Zn II sites. As expected, the Zn4 cluster displays high selectivity and sensitivity for sensing Cl − with low detection limits (LODs) in pure water (0.94 μM), HEPES biological buffer (1.44 μM), and real river water media (1.36 μM) by luminescent enhancement which are much lower than the minimum standards of drinking water enacted by the World Health Organization (WHO) and U.S. Environmental Protection Agency (USEPA) (7.05 mM). Additionally, the Zn4 cluster is also sensitive to histidine with low LODs in both pure water (0.83 μM), HEPES biological buffer (4.87 μM) and real river water samples (1.18 μM) through the luminescent quenching effect. Luminous test papers of the Zn4 cluster are made to provide a convenient, quick and real-time naked eye detection effect for sensing Cl − and histidine. The luminescence sensing mechanism of Cl − is further revealed via integrating several experiments with density functional theory (DFT) calculations. The results indicate that the Zn4 cluster is a promising material candidate for application in environmental monitoring.